Improving Project Practitioner Fit in Government Projects in Fujairah: Potential Implementations and Opportunities for Tamteen Philosophy and its Consequences - Al Mazrooei, Saleemah Abdullah (2016)
There are various academic and educational researches and studies that propose the concept of success/failure of construction and non-construction projects as well as the key factors and effects that determine this success/failure. Merely, one of these factors is the right selection of the right individuals to do the right jobs within organizations and/or projects in different business contexts and sectors. Significantly, this research aims at investigating the existence of the concept of fit in terms of selecting project managers/practitioners and its allied implementations in the public sector’s projects in Fujairah. This research review of literature considers the relevant aspects and propositions to the research’s aims and objectives through determining the relationship between following an effective selection criteria and achieving project success. Yet, knowing that project success examination is a challenge as there might not be a considered success criteria that is agreed upon and followed globally. Data collection and analysis has been conducted using qualitative research methods through conducting several interviews with decision-makers and projects’ managers in the targeted area of research, besides the use of three main project cases that have been studied and analyzed in a cross case analysis focusing on the implementation of selecting the right practitioners that help executing successful projects. The findings of the collected data have been discussed in the reflection of the interviews’ summaries and its key highlighted themes and aspects. Further, the research introduces “Tamteen” as a philosophy that might be effectively applicable in the public sector’s projects in Fujairah, starting from building a generalized recruitment system that can pave the way for considering project managers’/practitioners’ selection criteria in this sector in the future. The conclusion of this research study examines the potentiality of applying the concept of fit and/or Tamteen as success opportunity and proposes some recommendations that might be adapted.